Associação entre o ângulo de Norberg, o percentual de cobertura da cabeça femoral, o índice cortical e o ângulo de inclinação na displasia coxofemoral canina. - Giovana de Lima Toccafondo Vieira (2007)
The main goal of this study were to evaluate the association of factors such as Norberg and inclination angles, cortico-medullary index, percentage coverage of the femoral head, breed, sex and age to the development of canine hip dysplasia (CHD) in German Shepherd Dogs and Labrador Retrievers. 386 radiographs of the pelvis were evaluated, being 220 of German Shepherd Dogs (112 males e 108 females) and 166 of Labrador Retrievers (69 males e 97 females). The radiographs were graded for degree of dysplasia. The Norberg and inclination angles, cortico-medullary index and percentage coverage of the femoral head were measured and associated using multivariate statistical of principal components analysis. The frequency of hip dysplasia in German Shepherds Dogs was 83.6% and 63.3% in Labrador Retrievers. The incidence of CHD in both breeds studied was high. The results indicated that German Shepherds Dogs showed lower cortico-medullary index and CHD degree than those of Labrador Retrievers. The cortico-medullary index and inclination angle were inversely associated. The more the inclination angle, the less Norberg angle and percentage coverage of the femoral head. It was observed that with age, animals showed lower Norberg angles and percentage coverage of the femoral head, thus more CHD severity. Females were associated to lower femoral head coverage and Norberg angles, and more severe degree of CHD. Femoral inclination angle and cortico-medullary index did not demonstrate a correlation to CHD. Keywords: hip dysplasia, dog, radiology, principal component analysis